2013
DOI: 10.1159/000350834
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Stigma, Anxiety, Depression and Symptom Severity

Abstract: Objectives: Compared to other cancers, lung cancer patients report the highest levels of psychological distress and stigma. Few studies have examined the relationship between lung cancer stigma (LCS) and symptom burden. This study was designed to investigate the relationship between LCS, anxiety, depression and physical symptom severity. Methods: This study employed a cross-sectional, correlational design to recruit patients online from lung cancer websites. LCS, anxiety, depression and physical symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 58 publications
10
98
0
14
Order By: Relevance
“…They were affected in terms of anxiety and depression mostly because of the short life-expentancy (17). Cataldo et al also found high anxiety, depression and symptom severity in metastatic lung cancer patients (18). In another study conducted by Haun, not only lung cancer patients but also their partners are prone to high levels of depression and anxiety or severe distress related to the poor prognosis of the illness (19).…”
Section: Discussionmentioning
confidence: 95%
“…They were affected in terms of anxiety and depression mostly because of the short life-expentancy (17). Cataldo et al also found high anxiety, depression and symptom severity in metastatic lung cancer patients (18). In another study conducted by Haun, not only lung cancer patients but also their partners are prone to high levels of depression and anxiety or severe distress related to the poor prognosis of the illness (19).…”
Section: Discussionmentioning
confidence: 95%
“…SHIMIZU et al [71] were able to conclude, from their data from 1334 consecutive lung cancer patients (depression rate 12.4%), multifactorial patient-related contributors to the severity of depression, among which personal traits as well as coping style seemed to be the most relevant. Conversely, the work of CATALDO and BRODSKY [72] described a perceived lung cancer stigma by patients as an individual negative predictor for depression, anxiety and symptom severity. These circumstances strongly suggest a proactive outreach to lung cancer patients, especially at the time of diagnosis and during treatment.…”
Section: Psychological Dimensionmentioning
confidence: 99%
“…Para a construção da revisão integrativa é indispensável percorrer as seis etapas seguintes: identificação da questão de pesquisa, estabelecimento de critérios para inclusão e exclusão de estudos, definição das informações a serem extraídas dos estudos selecionados, avaliação dos estudos incluídos na revisão integrativa, tabela síntese dos estudos, interpretação dos resultados e síntese do conhecimento (Mendes, Silveira, Galvão, 2008;Whittemore, Knafl, 2005 Os objetivos dos estudos permearam a intenção dos pesquisadores em conhecer as percepções, experiências, temas-chaves, atitudes e crenças (Chapple, Ziebland, McPherson, 2004;Scott et al, 2015;Hamann et al, 2013;Brown-Johnson, Cataldo, 2013;Lehto, 2014;Marlow, Waller, Wardle, 2015) dos pacientes com câncer de pulmão, as relações entre estigma e vergonha, culpa, depressão, ansiedade, angústia, bem-estar, sintomas físicos, qualidade de vida e crescimento pós traumático (LoConte et al, 2008;Else-Quest et al, 2009;Gonzalez, Jacobsen, 2012;Cataldo, Jahan, Pongquan, 2012;Lebel et al, 2013;Cataldo, Brodsky, 2013;Brown-Johnson, Brodsky, Cataldo, 2014,;Shen et al, 2014,), os fatores que influenciam no atraso do relato dos sintomas e busca por atendimento (Tod, Craven, Allmark, 2008;Carter-Harris, 2015), desenvolver um instrumento para medir o estigma percebido (Cataldo et al, 2011), reduzir a Cataldo Lung Cancer Stigma Scale (Carter-Harris, Hall, 2014, traduzir e validar essa escala para os chineses (Yang et al, 2014) e descrever uma intervenção cognitivo-comportamental (Chambers et al, 2015). Estudo transversal descritivo com 93 pacientes e entrevista semiestruturada.…”
Section: Revisão Da Literaturaunclassified
“…Outro conceito que surge nos artigos (Cataldo et al, 2011;Cataldo, Jahan, Pongquan, 2012;Brown-Johnson, Cataldo, 2013;Cataldo, Brodsky, 2013;Shen et al, 2014) é o do estigma relacionado à saúde, que foi definido por Weiss e Ramakrishna (2006) como uma experiência pessoal caracterizada por exclusão, rejeição, culpa ou desvalorização decorrente da antecipação de um julgamento adverso.…”
Section: Conceituação De Estigmaunclassified
See 1 more Smart Citation